Green’s function formalism for highly correlated systems - Mancini, F.; Avella, A. (Condensed Matter Physics, 2006)
We present the Composite Operator Method (COM) as a modern approach to the study of strongly correlated
electronic systems, based on the equation of motion and Green’s function method. COM uses propagators of
composite operators as building blocks at the basis of approximate calculations and algebra constrains to fix
the representation of Green’s functions in order to maintain the algebraic and symmetry properties. Представлено метод композитних операторiв (МКО) у якостi сучасного пiдходу для дослiдження
сильноскорельованих електронних систем, що базується на методах рiвнянь руху та функцiй Грiна.
МКО використовує конструкцiї з пропагаторiв композитних операторiв для наближених розрахункiв,
а також алгебраїчнi умови для визначення представлення функцiй Грiна, щоб забезпечити алгебраїчнi та симетрiйнi властивостi.